1986
DOI: 10.1103/physrevlett.57.2123
|View full text |Cite
|
Sign up to set email alerts
|

Mass Shift of Charmonium near Deconfining Temperature and Possible Detection in Lepton-Pair Production

Abstract: The mass shift of charmonium near the critical temperature of the deconfining transition is investigated by a c-c potential model through the change of the string tension. On the basis of the results, detection of the shift by lepton-pair production is discussed by the use of the hydrodynamical model of ultrarelativistic nucleus-nucleus collisions. It is shown that the mass shift is detectable if the critical temperature is not lower than 300 MeV. PACS numbers: 12.38.Mh, 12.40.Ee, 12.40.Qq, 25.70.Np Althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
89
1

Year Published

1988
1988
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(92 citation statements)
references
References 21 publications
2
89
1
Order By: Relevance
“…In contrast to the effective model approaches, which have been extensively used to study the thermal properties of hadrons [2,6], only a few lattice QCD studies have been performed for the pole-mass of thermal hadrons so far [13,14,15,16]. Instead, the screening mass has been extensively studied with the lattice QCD [12,17,18,19] by analyzing the spatial correlations of the hadronic correlators.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast to the effective model approaches, which have been extensively used to study the thermal properties of hadrons [2,6], only a few lattice QCD studies have been performed for the pole-mass of thermal hadrons so far [13,14,15,16]. Instead, the screening mass has been extensively studied with the lattice QCD [12,17,18,19] by analyzing the spatial correlations of the hadronic correlators.…”
Section: Introductionmentioning
confidence: 99%
“…QCD at finite temperature is one of the most interesting subjects in the quark hadron physics [1,2,3]. At low temperature, quarks and gluons are confined in the color-singlet objects, hadrons, due to the nonperturbative effect of the strong interactions among them.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Changes of charmonium states have been regarded as one of the most important probes of plasma formation [1], because the potential model calculations predict the mass shift of charmonium near T c [2], and J/ψ suppression above T c [3]. However, lattice QCD simulations have indicated that the thermal properties of hadronic correlators are much more involved than weakly interacting almost free quarks [4].…”
Section: Introductionmentioning
confidence: 99%